Celluloid sermons : the emergence of the Christian film industry, 1930-1986 - Lindvall, Terry (New York University Press, 2011)
Christian filmmaking, done outside of the corporate Hollywood industry and produced for Christian churches, affected a significant audience of church people. Protestant denominations and individuals believed that they could preach and teach more effectively through the mass medium of film. Although suspicion toward the film industry marked many conservatives during the early 1930s, many Christian leaders came to believe in the power of technology to convert or to morally instruct people. Thus the growth of a Christian film industry was an extension of the Protestant tradition of preaching, wit.